H+ - O+ Coulomb Collision Frequency in the Polar Wind Plasma - Imad Barghouthi; Mazen Abu Issa; Mahmoud Abu Samra; Naji Qatanani (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
The polar wind is an ambipolar plasma outflow from the terrestrial ionosphere at high latitudes. As the ions drift upward along geomagnetic flux tubes, they move from collision-dominated to collisionless regions. A Monte Carlo simulation was used to calculate the temperature and Coulomb collision frequency in the polar wind. The simulation properly accounted for the divergence of geomagnetic field lines, the gravitational force, the polarization electric field, and Coulomb collisions. The temperature was found to increase with altitude and then decreases due to the interplay between frictional heating due to Coulomb collisions and adiabatic cooling (due to diverging geomagnetic field). The Coulomb collision frequency was found to decrease with altitude. As altitude increases, the ions are accelerated by the upward directed ambipolar electric field and become less coupled with the background ions. One of the objectives is to study the consequences of a velocity distribution function with an enhanced high energy tail for the injected ions. As the number of high energy ions increases in the tail of the velocity distribution at the injection point (i.e. kappa parameter decreases), the temperature increases and decreases.